Managerial Strategies for Curriculum Development in Sports, Nursing, and History Education Programs Based on Outcome-Based Education (OBE) and Research Findings - Lestari, Indah; Fahrizal, Fahrizal; Sumarjo, Sumarjo; Rahmi, Lisa; Amirzan, Amirzan (PT ARRUS Intelektual Indonesia, 2025)
This study investigates managerial strategies for curriculum development in sports science, nursing, and history education programs based on OBE and research findings. The research examines how program managers implement these strategies, the extent of research integration into curricula, and obstacles that affect curriculum effectiveness in producing professional graduates. This study employs qualitative data collected through in-depth interviews, participatory observation, and document analysis from three universities in Aceh, Indonesia. The participants included faculty deans, program heads, curriculum development team leaders, permanent faculty, and final-year students selected through purposive sampling. Data collection focused on managerial practices, stakeholder involvement, theory-practice integration, and research incorporation into curriculum development processes. The collected data was analyzed using interactive data analysis techniques involving data reduction, presentation, and conclusion drawing. The results show that three main managerial strategies are currently implemented: stakeholder-inclusive curriculum development involving both internal and external stakeholders, competency-based curriculum design structured around measurable learning outcomes, and theory-practice integration mechanisms through mandatory collaboration between theoretical and practical course instructors. However, three primary challenges emerged: research-curriculum misalignment reported by 78% of faculty, faculty workload imbalance identified by 85% of respondents, and industry-academia gaps noted by 67% of program administrators. Research integration showed varying implementation levels, with systematic approaches demonstrating higher effectiveness than ad-hoc methods. The findings suggest that effective OBE-based curriculum management requires systematic research-curriculum alignment mechanisms, flexible faculty role definitions supporting research-teaching integration, and ongoing industry partnerships informing both research directions and curricular content. Success depends on institutional commitment to developing coherent systems rather than implementing isolated practices